Hypocretin receptor antagonists for insomnia: rationale and clinical data. (June 2012) - Ruoff, Chad; Guilleminault, Christian
Loss of hypocretin neurons leads to sleep attacks and cataplexy in a rare sleep disorder known as narcolepsy. The hypocretin system stabilizes states of wakefulness and sleep through complex neural pathways. Insomnia, on the other hand, is a common sleep disorder characterized as difficulty initiating or maintaining sleep. Current treatment options for insomnia are limited to cognitive-behavioral therapy and pharmacological agents such as non-benzodiazepine receptor agonists. The discovery of hypocretin and deficiency of these peptides in narcolepsy spurred the development of pharmacological agents that antagonize hypocretin receptors for the treatment of sleep disorders such as insomnia. Preclinical and limited clinical data on hypocretin antagonists have shown favorable outcomes in the treatment of insomnia but concerns of theoretical adverse effects still remain.